2023
DOI: 10.1002/jmv.28769
|View full text |Cite
|
Sign up to set email alerts
|

Presymptomatic viral shedding in high‐risk mpox contacts: A prospective cohort study

Abstract: The risk of infection after exposure to clade IIb mpox virus (MPXV) is unknown, and potential presymptomatic shedding of MPXV remains to be demonstrated. High-risk contacts of mpox patients were followed-up in a prospective longitudinal cohort study. Individuals reporting sexual contact, >15 min skin-to-skin contact, or living in the same household with an mpox patient were recruited in a sexual health clinic in Antwerp, Belgium. Participants kept a symptom diary, performed daily self-sampling (anorectal, geni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The average mpox incubation period of just over a week 39 may be short enough that memory B cells and memory T cells can activate and protect an exposed human even in the absence of circulating neutralizing antibodies. How waning of antibodies impacts transmission is also an open question as recent work has revealed that viral DNA and culturable virus is present in infected individuals as early as 4 days prior to symptom onset 40 . Our finding here that a longer dosing interval increases neutralizing titer durability among naïve vaccinees differs from our previous work where we reported that there was no significant effect of interval on durability of anti-MPXV H3 IgG titers in naïve individuals 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The average mpox incubation period of just over a week 39 may be short enough that memory B cells and memory T cells can activate and protect an exposed human even in the absence of circulating neutralizing antibodies. How waning of antibodies impacts transmission is also an open question as recent work has revealed that viral DNA and culturable virus is present in infected individuals as early as 4 days prior to symptom onset 40 . Our finding here that a longer dosing interval increases neutralizing titer durability among naïve vaccinees differs from our previous work where we reported that there was no significant effect of interval on durability of anti-MPXV H3 IgG titers in naïve individuals 7 .…”
Section: Discussionmentioning
confidence: 99%
“…We used an SEIR (susceptible, exposed, infectious, resistant) natural history in our model, expanded to account for pre-symptomatic transmission and multi-dose vaccination [6]. Individuals start in the susceptible ( S ) class.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 Furthermore, presymptomatic (1−4 days before symptom onset) viral shedding of replication-competent MPXV has been reported. 7 In experimental settings, MPX-virions could be recovered from stainless steel for several days, but were efficiently inactivated by alcohol-or aldehyde-based surface disinfectants. 8 In hospital settings, environmental surface contamination with high MPXV-loads and cultivatable virus was shown on surfaces of rooms occupied by Mpox patients.…”
Section: Lack Of Monkeypox Virus (Mpxv) Transmission Despite Occupati...mentioning
confidence: 99%